PENGALAMAN MASYARAKAT PAKPAK BHARAT MERAWAT LUKA MENGGUNAKAN KEMENYAN - Minta Ito Melinda Harahap (Universitas Prima Indonesia, 2019)
A wound is a broken continuity or anatomical connection of tissue in the body of a living being. Management of wound healing can be given conventional therapy or with complementary therapy. Wound healing with complementary therapy that is still used by the Indonesian people for wound healing, one of which is frankincense. The Pakpak Bharat community uses incense as a medicine to heal wounds. This study aims to explore in deeply the meaning of Pakpak Bharat's community experience in healing wounds using incense. This research is a phenomenological study. Data were collected through in depth interview. Participants in this study were 20 people who were selected by purposive sampling technique. Data analysis in this research was done by content analysis. Results of analysis found 3 (tree) themes, namely: how to use incense, length of use of incense, type of wound that uses incense.. In general, people do not know the function and benefits of incense for healing wounds, people only use it for generations and there is no information from health workers. Based on the results of the study, health workers are advised to provide information about wound care.